Who participates in a randomized trial of mindfulness‐based stress reduction (MBSR) after breast cancer? A study of factors associated with enrollment among Danish breast cancer patients. Issue 5 (16th May 2012) - Würtzen, Hanne; Dalton, Susanne Oksbjerg; Andersen, Klaus Kaae; Elsass, Peter; Flyger, Henrik Lavlund; Sumbundu, Antonia; Johansen, Christoffer
Abstract Background Discussion regarding the necessity to identify patients with both the need and motivation for psychosocial intervention is ongoing. Evidence for an effect of mindfulness‐based interventions among cancer patients is based on few studies with no systematic enrollment. Methods We used Danish population‐based registries and clinical databases to determine differences in demographics, breast cancer and co‐morbidity among 1208 women eligible for a randomized controlled trial (www.clinicaltrials.gov identifier: NCT00990977) of mindfulness‐based stress reduction MBSR. Results Participants (N = 336) were found to be younger (p < 0.001) and have a less recent diagnosis at invitation than decliners (N = 872; p < 0.001). After adjustment for age and time since diagnosis at invitation, a statistically significant difference was also found between the two groups in use of psychologist sessions (p < 0.05), whereas neither breast cancer variables nor co‐morbidity was significantly different. Self‐reported data obtained by use of validated psychometric scales from 169 decliners and 336 women who agreed to enroll in the trial showed statistically significant differences in level of education, distress, anxiety, depression, well being and symptom burden. No differences were observed with regard to marital status, children living at home, affiliation to the work market, psychiatric caseness or any lifestyle measure. Conclusion Our findings indicate that participants are younger, have a less recent diagnosis and have a higher level of education than those who refuse. This should be taken into account in designing and evaluating trials of psychosocial interventions and in planning mindfulness‐based interventions. Copyright © 2012 John Wiley & Sons, Ltd.